201k views
4 votes
Which expression is equivalent to (3^2)^-2

2 Answers

7 votes

Answer: 1/81

First you simplify it to 3^-4

Then express it with a positive exponent which goes to 1/3^4

Then evaluate it to 1/81

User Sphinx
by
6.2k points
5 votes

Answer:

The expression which is equivalent to the given expression is given by :


\bf(1)/(81)

Explanation:

The expression is given to be :


(3^(2))^(-2)

Now, we need to find a expression which is equivalent to this given expression.


(3^(2))^(-2)\\\\\implies (3* 3)^(-2)\\\\\implies (9)^(-2)\\\\\implies(1)/((9)^2)\\\\ \implies (1)/(81)

Hence, The expression which is equivalent to the given expression is given by :


\bf(1)/(81)

User Dodger
by
5.5k points